Global evolution of research on green energy and environmental technologies:A bibliometric study - Tan, Hao; Li, Jialing; He, Min; Li, Jiayu; Zhi, Dan; Qin, Fanzhi; Zhang, Chen (Journal of environmental management, 2021)
To better grasp developments and trends in research on green energy and environmental technologies, the published literatures in the Web of Science Core Collection database from 1998 to 2020 were utilized to reveal critical information and guidance on what has been investigated, and what are the changes in research interests using a bibliometric method. Herein, yearly quantitative distribution of literatures, author contribution and collaboration, productive and influential institutions and countries/territories, co-citation analysis, keywords co-occurrence analysis, and research frontier identification are analyzed via information visualization technology. The results show that the publications on green energy and environmental technologies have grown exponentially, that China, the USA, and Italy are the most active countries, but the global cooperation is not close at present. The research frontier identification results reveal that the categories of energy, wastewater, and performance remain stable, while the trending up and emerging categories of catalyst and CO2 emission show clear shift over the last decade, indicating that catalytic production of clean energy and value-added chemicals, strategies to reduce greenhouse gas emissions, and other related studies to solve the global energy crisis and environmental problems are the research frontiers. This bibliometric study provides unique insights and offers research guidance on green energy and environmental technologies. ●A bibliometric method is used to analyze the studies in green energy and environmental technologies●Author contribution and collaboration have been studied via mapping knowledge domain●Co-citation analysis has been used to analyze the research status●The current frontiers of green energy and environmental technologies are visually explored